On the application of modified cuckoo optimization algorithm to the crack detection problem of cantilever Euler–Bernoulli beam. (September 2015) - Moezi, Seyed Alireza; Zakeri, Ehsan; Zare, Amin; Nedaei, Mehrshad
Highlights: The location and depth of a crack in a beam is predicted by measuring the changes in its natural frequencies. The crack is replaced by a torsion spring in an Euler–Bernoulli beam. Three optimization algorithms, COA, GA–NM and MCOA algorithm are utilized. Experimental tests are setup to verify the accuracy of the optimization methods. The results show better performance of MCOA than other methods. Abstract: Crack in any structure changes its natural frequencies. Therefore it is possible to determine the location and depth of crack by measuring its natural frequency changes. In this study, the application of MCOA numerical method for open edge-crack detection in an Euler–Bernoulli cantilever beam is proposed. The crack is modeled by a torsional spring, the coefficient of which is calculated using the crack dimensions. The objective function is the weighted squares difference of the measured and calculated natural frequencies. The results of the numerical simulations and experimental tests reveal high accuracy in detecting the location and depth of the crack.